Does acetabular coverage influence the clinical outcome of arthroscopically treated cam-type femoroacetabular impingement (FAI)?. (July 2018) - Ibrahim, M. M.; Poitras, S.; Bunting, A. C.; Sandoval, E.; Beaulé, P. E.
Abstract : Aims: What represents clinically significant acetabular undercoverage in patients with symptomatic cam-type femoroacetabular impingement (FAI) remains controversial. The aim of this study was to examine the influence of the degree of acetabular coverage on the functional outcome of patients treated arthroscopically for cam-type FAI. Patients and Methods: Between October 2005 and June 2016, 88 patients (97 hips) underwent arthroscopic cam resection and concomitant labral debridement and/or refixation. There were 57 male and 31 female patients with a mean age of 31.0 years (17.0 to 48.5) and a mean body mass index (BMI) of 25.4 kg/m 2 (18.9 to 34.9). We used the Hip2Norm, an object-oriented-platform program, to perform 3D analysis of hip joint morphology using 2D anteroposterior pelvic radiographs. The lateral centre-edge angle, anterior coverage, posterior coverage, total femoral coverage, and alpha angle were measured for each hip. The presence or absence of crossover sign, posterior wall sign, and the value of acetabular retroversion index were identified automatically by Hip2Norm. Patient-reported outcome scores were collected preoperatively and at final follow-up with the Hip Disability and Osteoarthritis Outcome Score (HOOS). Results: At a mean follow-up of 2.7 years (1 to 8, sd 1.6), all functional outcome scores significantly improved overall. Radiographically, only preoperative anterior coverage had a negative correlation with the improvement of the HOOS symptom subscale (r = -0.28, p = 0.005). No significant difference in relative change in HOOS subscale scores was found according to the presence or absence of radiographic signs of retroversion. Discussion: Our study demonstrated the anterior coverage as an important modifier influencing the functional outcome of arthroscopically treated cam-type FAI. Cite this article: Bone Joint J 2018;100-B:831–8.